Synthesis, Characterization and Photocatalytic Properties of Non-peripherally 3- (pyridin-4-yl) propane-1-oxy Groups Substituted Cu (II) Phthalocyanine and Water Soluble Derivative - Ece Tuğba Saka (Sakarya Üniversitesi Fen Bilimleri Enstitüsü Dergisi, 2020)
Cu (II) phthalocyanine compound and its water-soluble derivative containing 3- (pyridin-4-yl) propane-1-oxy groups in non-peripheral positions were synthesized for the first time and their structures were elucidated. The photocatalytic properties of Cu (II) phthalocyanine compounds, which were synthesized and characterized, were investigated on the photocatalytic degradation reactions of 4-nitrophenol, one of the important environmental pollutants. In the photocatalysis reactions that took place in the photoreactor for 2 hours without using any oxidant, 4-nitrophenol compound was completed with 94.4% and 98.6% conversion to toxic and non-harmful species. The hydroquinone compound was identified as the main product and the benzoquinone compound as the by-product. The conversion number for the non-peripheral Cu (II) phthalocyanine compound and its water-soluble derivative was 471 and 488 and the conversion frequency was 235.5 and 244,0 respectively. Finally, recovery studies were carried out for water soluble Cu (II) phthalocyanine used as photocatalyst and the number of cycles was determined as 5.